Development of multiband Fractal planar inverted F antenna (F-PIFA) for mobile applications - Saidatul Norlyana, Azemi
In the past few years, demand in unification of wireless hardware has propelled new development of antenna. With the advances on antenna technology, it becomes attractive to enhance the capabilities of antenna in many areas such as mobile communication and wireless application. The requirements of ubiquitous antenna are small in size, simple, robust, have a shielding mechanism, multisystem and wide bandwidth. The reason is, currently, there are five bands that are assigned for world mobile services. Due to the aforementioned issues, a novel Fractal planar inverted F antenna (F-PIFA) based on the self affinity design is presented in this research. This research is conducted in order to develop an antenna with low cost, small in size, high performance, and capable to operate at multiple frequency bands. The F-PIFA development processes include specification definition, selection of the dielectric material and construction of prototype using CST software tools. In conducting this research, the production of prototypes is divided into three stages. The first stage is to develop three different iteration of F-PIFA and to evaluate its performance. The second stage is to fabricate, measure the antenna performance as well as the SAR value. Finally, the design is investigated and improved for future works. This research has successfully produced an antenna with good efficiency without degrading bandwidth and gain of the F-PIFA. The antenna has a total dimension of 27mm x 27mm is designed and optimized in order to receive GSM (Global System for Mobile Communication) and UMTS (Universal Mobile Telecommunication System) and HiperLAN (HigH Performance Radio LAN) with the frequency range from 850-960 MHz, 1900 MHz to 2100 MHz, 1885 to 2200 MHz for 3G and 4800 MHz to 5800 MHz for HiperLAN respectively. This omni-directional antenna invented here have 65-90% efficiency with peak gain value that is 3.57 dB, and be able to produce less than 2W/kg SAR value.